A Cross-sectional Study to Evaluate Diabetes Management, Control and Complications in Patients with type 2 Diabetes in Bangladesh (BIRDEM Medical Journal, 2017)
Background: Management of type 2 diabetes is not uniform. The aim of the study was to assess diabetes care delivery and status of long-term diabetes related complications.Methods: DiabCare is an observational, non-interventional, cross-sectional study of hospital-based outpatient type 2 diabetes care.Results: A total of 2092 patients participated in the study: mean age 51.3±11.0 years, and duration of diabetes 7.6±5.4 years. The patients were almost equal in both genders (male: 49.8% vs. female: 50.2%) and the largest homogenous ethnic group was Bangladeshi (99.6%). The percentage of patients with HbA1c < 7.0% (< 53 mmol/mol) was 22.5% and mean HbA1c was 8.8±2.2 %. The proportion of patients using insulin was 58.0% (n=1214) at a total daily dose of 34.4±14.7 IU. The most common diabetes related complications were: Peripheral neuropathy (39.0%) and eye complications (21.7%). Duration of diabetes was associated with higher odds of CV complications, diabetic nephropathy and eye complications [adjusted OR 1.03, p=0.007; 1.05, p